Evaluation of bacterial cellulose/quince seed mucilage composite scaffold for wound dressing - ÜNAL YILDIRIM, SEMRA; GÜNDÜZ, OĞUZHAN (My University, 2022)
Bacterial cellulose (BC) and quince seed mucilage are very promising biological materials. In this study, we reported the design and fabrication of a novel biocompatible scaffold with excellent fibroblast cell proliferation, making it a promising composite scaffold for wound dressings. The composite scaffold was fabricated by ex situ modification of bacterial cellulose by quince seed mucilage. The products were investigated to determine their morphological features, chemical features, and thermal and swelling behaviors. Cell culture and proliferation tests were performed to obtain information on biocompatibility of the scaffolds. This work indicates the novel scaffold provides great potential in wound dressing for clinical application.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Metals and Alloys; Materials Chemistry; General Materials Science; Physical Sciences; Bacterial cellulose; Quince seed mucilage; Skin tissue engineering; Scaffold; Cellulose dressing; QUINCE; NANOCOMPOSITES; EXTRACTION; MEMBRANES; HYDROGEL